DAMPAK TRANSFER PRICING, THIN CAPITALIZATION, DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE - Asdayani Aryanti (2022)
This study was conducted to examine and analyze the impact of transfer pricing, thin capitalization, and financial distress on tax avoidance in multinational companies manufacturing sector listed on the Indonesia Stock Exchange in 2018-2020. The technique used is purposive sampling and obtained as many as 165 samples. This type of research is quantitative using secondary data sourced from annual reports and company financial statements. The data analysis technique used is multiple linear regression analysis using the software program Stata Version 14.2. The results of the study indicate that Transfer Pricing and Financial Distress have no significant effect on Tax Avoidance, which indicates that high or low Transfer Pricing and Financial Distress do not encourage companies to undertake Tax Avoidance. The next result, Thin Capitalization has a significant negative effect on Tax Avoidance, indicating that the higher the Thin Capitalization carried out by the company, the lower the practice of Tax Avoidance.